2005
DOI: 10.1016/j.jfineco.2003.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The timing of initial public offerings

Abstract: We study the dynamics of IPOs by examining the tradeoff between an entrepreneur's private benefits, which are lost whenever the firm is publicly traded, and the gains from diversification. We characterize the timing dimension of the decision to go public and its impact on firm value and the evolution of firm risk over time. By endogenizing the timing of the decision to go public, we explain the clustering of IPOs and buyouts in time, the industry concentration of IPO waves, the high incidence of reprivatizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(116 citation statements)
references
References 32 publications
4
110
0
2
Order By: Relevance
“…Our findings are consistent with rational listing decisions in a standard CAPM-pricing context, where the listing decision depends upon the trade-off between diversification (Pagano, 1993;Benninga, Helmantel, and Sarig, 2005;Pastor, Taylor, and Veronesi, 2009) and private benefits of control (Dyck and Zingales, 2004). Alternatives factors related to the value of a firm (e.g., size, growth opportunities, etc.)…”
Section: Introductionsupporting
confidence: 81%
“…Our findings are consistent with rational listing decisions in a standard CAPM-pricing context, where the listing decision depends upon the trade-off between diversification (Pagano, 1993;Benninga, Helmantel, and Sarig, 2005;Pastor, Taylor, and Veronesi, 2009) and private benefits of control (Dyck and Zingales, 2004). Alternatives factors related to the value of a firm (e.g., size, growth opportunities, etc.)…”
Section: Introductionsupporting
confidence: 81%
“…While the role and efficacy of regulation in capital markets are still in dispute both in academia and practice, we test the effect of a market shut down on the IPO underpricing in China, as well as the effect of micro-factors, such as firm size and volume of the IPO issuance at the firm level, and macro-factors, such as the overall IPO market returns before the IPO of a firm. Chen et al (2015) recently reported that the lead-lag relationship between the initial returns and the volume of IPOs is not statistically significant due to institutional differences in the Chinese IPO markets, even though the IPO volume is sensitive to changes in market conditions (Pastor and Veronesi, 2005;Benninga et al, 2005;Yung et al, 2008), and investor sentiment (Ljungqvist et al, 2006;Bustamante, 2012), theoretically. They claim, in China, that the CSRC substantially controls IPO timing, the IPO volume does not respond to changes in market conditions or sentiment as in market-driven economies, and there is no statistically significant relationship between the IPO volume and past market returns, volatility, and valuations in China.…”
Section: A Ipos In Chinese Marketsmentioning
confidence: 99%
“…First, the rational market-timing theory or 'the window of opportunity', suggests that due to agency problems between managers and investors, managers have incentives to postpone their IPO when their securities are undervalued, until the bull market arrives for more favorable pricing (Lucas and McDonald, 1990;Graham and Harvey, 2001). Second, the life cycle theory suggests that a firm finds optimal timing in their life cycle to go public after its early life cycle as a private firm (Chemmanur and Fulghieri, 1999;Benninga et al, 2005). In addition to firm-level micro approaches, some prior research on IPO underpricing uses macroeconomic factors, like the stock market and bond market performances for a three-month period before the IPO (Bayless and Chaplinsky, 1991), other macroeconomic variables, including the term spread, default spread, and three-month equity market return prior to the IPO (Korajczyk and Levy, 2003), and more recently legal protection and a country's accounting disclosure standards (Wang, 2011).…”
Section: B Ipo Underpricingmentioning
confidence: 99%
“…The structure of this paper is as follows: Section 2 presents the implications of Benninga-Helmantel-Sarig (2005) model and studies its implications on employee stock option pricing. Section 3 presents the employee stock option sample database.…”
Section: Introductionmentioning
confidence: 99%